Assessing the economic ripple effects of critical infrastructure failures using the dynamic inoperability input-output model: A case study of the Taal volcano eruption - Santos, Joost (Animo Repository, 2023)
Critical infrastructure systems are essential in sustaining people’s livelihoods and the operation of economic sectors. In this paper, we extend the dynamic inoperability IO model (DIIM), we evaluate the resilience of economic sectors given the initial functionality loss and recovery time of an infrastructure. The resulting model is applied in a case study of the 2020 eruption of Taal Volcano in the Philippines. The initial inoperability and recovery period parameters are used in the 14-sector DIIM. The dynamic recovery behaviors of the sectors are plotted over the disaster timeline based on two metrics: (1) economic loss, which is the monetary value of the damage; and (2) inoperability, which is the dimensionless loss relative to the total production output of each sector. The DIIM template and case study results from this paper can provide policy insights to enhance disaster resilience planning for future disasters.